IMPLEMENTATION OF DIGITAL SIGNATURE IN WEB TO IMPROVE THE QUALITY OF MANAGEMENT INFORMATION SYSTEMS IN EDUCATION SECTOR - Halili, Arbnor; Rexha, Blerim; Aliu, Albert (European Scientific Journal, ESJ, 2014)
Information technology is becoming the world’s most influential factors in everyday life. It has even large economic impact in family and state budget. Web software systems, due to their friendly network configuration and hardware independence properties ate gaining more and more user acceptance. But, in web systems the authenticity of transmitted and stored data is still an open challenge. This paper aims to give the answer to these questions using digital certificates, as defined by ISO X.509 standard, for encrypting communication channel and digitally signing student data for archiving. The implementation of digital signatures on the web has special challenges. Digital signature uses digital certificate of the current user, which certificate is stored in userâ€™s local store or file and it has restricted access. This paper presents an implementation web digital signature in two different platforms: (i) using Microsoft browser, and (ii) non-Microsoft browser and comparing their properties, functionality and efficiency. This paper, furthermore, describes in detail the implementation of the digital signature on the web starting from the definition of the problem up to the technical implementation, including as a case study the Student Management System installed at the Faculty of Electrical and Computer Engineering, University of Pristina